Victim support and prevention of secondary victimisation: Contemporary legal solutions and practice - Ristanović-Nikolić Vesna (Temida)
The main aim of this paper is to assess results of victim oriented reforms in both international and national laws and practice, as well as to identify the best practice which may be used as a model for reforms regarding rights of crime victims in Serbia. Thus the solutions included in main international documents regarding crime victims as well as in European and US laws are analysed. On the bases of this analysis, the best practice as well as the relationship between it and the situation in Serbia is identified. Finally, the recommendations for changes of laws and practice, which would bring Serbia closer to best practice, are proposed.